2021
DOI: 10.3390/f12030263
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Epicotyl Physiological Dormancy in the Recalcitrant Seed of Quercus chungii F.P.Metcalf with the Elongated Cotyledonary Petiole

Abstract: Control of seed germination and dormancy is important in seed plant adaptation and evolution. When studying seed dormancy of Quercus species, we observed a substantially delayed shoot emergence following a fast root emergence in Quercus chungii F.P.Metcalf. Since epicotyl physiological dormancy (PD) has not been reported in Quercus section Cyclobalanopsis, we examined seed morphology and germination in Q. chungii and aimed to document epicotyl PD in the seeds. The embryo was fully developed in fresh ripe seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Although only based on two CTB species, this pattern of rapid germination is consistent with previous literature for Q. chungii and Q. kerrii from the lineage (e.g. Xu et al, 2019;Sun et al, 2021).…”
Section: Bet-hedging Strategies In Subtropical Oak Seedssupporting
confidence: 90%
See 1 more Smart Citation
“…Although only based on two CTB species, this pattern of rapid germination is consistent with previous literature for Q. chungii and Q. kerrii from the lineage (e.g. Xu et al, 2019;Sun et al, 2021).…”
Section: Bet-hedging Strategies In Subtropical Oak Seedssupporting
confidence: 90%
“…prinus and Q . robur (McCartan et al ., 2015; Sun et al ., 2021), which occur in cold dry regions of North America and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in many oak species, the epicotyl is carried just outside the apex of the acorn via elongation of the cotyledonary petioles prior to shoot elongation (Rowlee and Hastings, 1898;Pammel and King, 1917;Korstian, 1927;Jones, 1959;Molinas and Verdaguer, 1993;Pascual et al, 2002;Sung et al, 2010;Yi et al, 2012Yi et al, , 2013Yi et al, , 2019. Furthermore, in some species of Quercus, including Q. chungii (Sun et al, 2021), Q. engelmannii (Snow, 1991), S. semecarpifolia (Troup, 1921;Shrestha, 2003) and Q. virginiana (Engelmann, 1880;Lewis, 1911;Coker, 1912), the cotyledonary tube (formed by fusion of cotyledonary petioles) carries/pushes the embryonic axis up to several centimetres from the apex of the acorn. Troup (1921) says that in Q. semicarpifolia '… the tube may thus attain a length of as much as 4 in [10 cm] or even more'.…”
Section: Epicotyl Pdmentioning
confidence: 99%
“…Thus, it seems likely that the acorns of this species have epicotyl PD. Recently, Sun et al (2021) have clearly demonstrated that seeds of Quercus chungii from subtropical southern China have epicotyl PD.…”
Section: Do Tropical/subtropical Species Of Fagaceae Have Epicotyl Pd?mentioning
confidence: 99%
“…An important ecological adaptation is seed dormancy, which allows dispersal in time and space and which prevents the simultaneous germination of all new produced seeds [13]. Sun et al [14] examined both seed morphology and germination in Quercus chungii (syn. Cyclobalanopsis chungii) and they aimed to describe seed dormancy.…”
mentioning
confidence: 99%